1996
DOI: 10.1111/j.1365-2648.1996.tb03149.x
|View full text |Cite
|
Sign up to set email alerts
|

Situating theory in practice: student views of theory‐practice in Project 2000 nursing programmes

Abstract: In this paper the views of student nurses taking Project 2000 at a Scottish College of Nursing are reported. A random sample of 19 students were interviewed. The interviews focused on the relationship between the college course and the students' experiences on placement. The majority had difficulty in relating the college course to their practice, except when it came to very specific parts of the programme, for example basic medical procedures. Only a minority could integrate the broader aspects of the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…Students, particularly those on the Common Foundation Programme appeared to have particular difficulty in making sense of the theory taught in college and relating it to practice ( Davies et al . 1996 , Hislop et al . 1996 , Philips et al .…”
Section: Resultsmentioning
confidence: 99%
“…Students, particularly those on the Common Foundation Programme appeared to have particular difficulty in making sense of the theory taught in college and relating it to practice ( Davies et al . 1996 , Hislop et al . 1996 , Philips et al .…”
Section: Resultsmentioning
confidence: 99%
“…I do not mean that faculty had little command of these theories, but rather they did not enact effective pedagogical techniques to explain them. Here, it is important to emphasize the disconnect between theory and practice and its implications for nursing faculty and students, an issue that continues to elicit much research and debate in the nursing literature (Barger 1998;Davies 1995b;Hislop et al 1996;McCaugherty 1991;McHugh et al 1996;Oermann 1998;Porter and Ryan 1996). In my interviews, faculty suggested that students are not prepared to understand sophisticated theory in general, and theories of caring in particular.…”
Section: Holistic Care and Its Missing Dimensionmentioning
confidence: 89%
“…The tension between vocational and academic learning has been a subject of long-standing debate and is being specifically addressed by the Unified Learning Project funded as part of the ESRC Learning Society Programme (Young et al 1997). This debate has particular relevance in the education of health care staff (Elkan and Robinson 1995, Hewison and Wildman 1996, Hislop et al 1996. In the higher education climate the tension between providing hospital trusts with individuals 'fit to practice' versus meeting the academic standards of HE-validated courses may be particularly acute.…”
Section: The Nhs and Formal Learningmentioning
confidence: 98%